Intelligent ISSA-Based Non-Singular Terminal Sliding-Mode Control of DC–DC Boost Converter Feeding a Constant Power Load System - Lu Liu; Yun Zeng (Energies, 2023)
In response to the issue of system oscillations in direct current (DC) microgrid systems with constant power loads (CPL), this paper proposes a non-singular terminal sliding-mode control (NTSMC) strategy based on the improved salp swarm algorithm (ISSA). Firstly, the state-feedback exact linearization technique is employed to establish a linearized model of the converter system. Then, the NTSMC based on a composite sliding-mode surface is designed to achieve rapid convergence and effectively weaken the chattering issue in traditional sliding-mode control, ensuring a constant power supply to the load. The parameters of the proposed NTSMC are optimized using the ISSA, which introduces an intelligent NTSMC. Finally, a MATLAB/Simulink simulation model is established. The simulation results show that the ISSA-based composite sliding-mode surface NTSMC system designed for DC microgrid systems with CPL exhibits high robustness and guarantees ideal steady-state characteristics and dynamic responses when input voltage fluctuations and load disturbances occur.